A study on the response of the Equatorial Ionization Anomaly over the East Africa sector during the geomagnetic storm of November 13, 2012. Issue 12 (15th June 2015) - Joseph, Olwendo Ouko; Yamazak, Yosuke; Cilliers, Pierre; Baki, Paul; Ngwira, Chigomezyo M.; Mito, Collins
Highlights TEC observations are indicators of ionospheric variability over time. Diurnal and annual variations in TEC reflect ionospheric conditions over time. Ionospheric variability can be influenced by Geomagnetic storms. Ionization crests gets modified during storms by the penetration electric fields.